Using Lactobacilli to Fight Escherichia coli and Staphylococcus aureus Biofilms on Urinary Tract Devices - Fábio M. Carvalho; Filipe J. M. Mergulhão; Luciana C. Gomes (MDPI AG, 2021)
The low efficacy of conventional treatments and the interest in finding natural-based approaches to counteract biofilm development on urinary tract devices have promoted the research on probiotics. This work evaluated the ability of two probiotic strains, Lactobacillus plantarum and Lactobacillus rhamnosus, in displacing pre-formed biofilms of Escherichia coli and Staphylococcus aureus from medical-grade silicone. Single-species biofilms of 24 h were placed in contact with each probiotic suspension for 6 h and 24 h, and the reductions in biofilm cell culturability and total biomass were monitored by counting colony-forming units and crystal violet assay, respectively. Both probiotics significantly reduced the culturability of E. coli and S. aureus biofilms, mainly after 24 h of exposure, with reduction percentages of 70% and 77% for L. plantarum and 76% and 63% for L. rhamnosus, respectively. Additionally, the amount of E. coli biofilm determined by CV staining was maintained approximately constant after 6 h of probiotic contact and significantly reduced up to 67% after 24 h. For S. aureus, only L. rhamnosus caused a significant effect on biofilm amount after 6 h of treatment. Hence, this study demonstrated the potential of lactobacilli to control the development of pre-established uropathogenic biofilms.